Institutionalizing Community Engagement in Higher Education: A Quantitative Approach to Identifying Patterns of Engagement Based on Institutional Characteristics - Hutson, Natasha Lee (My University, 2016)
The purpose of this research study was to explore the depth to which colleges and universities in the state of Georgia have institutionalized community engagement into their campus infrastructures. Community engagement was operationalized using the Furco, Weerts, Burton, and Kent (2009) model for institutionalizing community engagement in which there are five dimensions of engagement: Mission and Philosophy, Faculty Support and Involvement, Student Support and Involvement, Community Participation and Partnership, and Institutional Support. A survey design was used to collect data on trends in institutionalized community engagement at sample institutions (N = 48). A factor analysis statistical procedure indicated patterns of engagement in Georgia’s higher education institutions that generally mirrored the Furco et al. (2009) model of the five dimensions of community engagement. Results of a multivariate analysis of variance (MANOVA) test indicated no difference in the dimensions of community engagement based on institutional type (2-year/4-year) or control (public/private). However, ordinary least squares (OLS) regression analyses results showed that institutional characteristics were a significant predictor of one dimension of community engagement, Institutional Support. Similarly, a logistic regression analysis further indicated that Faculty Support (B = .624, p ≤ .05) and Institutional Commitment (B = .267, p ≤ .10) dimensions were significant predictors of institutional receipt of the Carnegie Engaged Campus Classification, the President’s Higher Education Honor Roll in Community Service, or both designations. In addition, Institution Type (B = -2.487, p ≤ .10) had a moderately significant negative predictive power, indicating that the odds of receiving national recognition were decreased by 8% for 2-year institutions. The final logistic regression model accurately predicted 85.4% of the cases. Implications for higher education in the state of Georgia include the urgent need to establish a Campus Compact coalition to more comprehensively research community engagement in the state and identify best practices and support mechanisms for engagement across the state. Additionally, university leaders must be intentional in developing campus-community partnerships by implicitly and explicitly supporting the community work of faculty, students, and staff through the allocation of resources, rewards, and recognition. Lastly, institutional leaders should increase campus efforts to create campus environments that provide transformative teaching and learning experiences for students, faculty, and staff.
Chapter I: INTRODUCTION..1 | Purpose.6 | Problem Statement...7 | Significance..7 | Research Questions..8 | Chapter II: REVIEW OF THE LITERATURE...9 | Defining Community Engagement..9 | Earnest Boyer: The Scholarship of Engagement.......12 | Renewing Higher Educations’ Commitment to Community Engagement 14 | The Wingspread Conferences 14 | A Crucible Moment...16 | Student Learning Outcomes of Community Engagement.18 | The Furco Rubric for Institutionalizing Community Engagement....20 | Mission and Philosophy.21 | Faculty Support for and Involvement ...23 | Promotion, Reward, and Tenure 23 | Student Support for and Involvement ...25 | Community Participation and Partnerships...27 | Institutional Support ..29 | Leadership..29 | Infrastructure..30 | Funding....32 | Institutional Characteristics...32 | The Carnegie Engaged Institution Designation.34 | The National President’s Higher Education Community Service Honor Roll..35 | National Investors in Community Engagement.36 | Campus Compact...36 | Corporation for National and Community Service 37 | Current State of Community Engagement.38 | Theoretical Framework..40 | Chapter III: METHODOLOGY.43 | Methods..44 | Population..44 | Study Sample.46 | Research Design.48 | Ethical Considerations...48 | Survey Instrument..49 | Data Collection Procedures....53 | Study Variables..56 | Dependent Variables..56 | Independent Variables...60 | Supplemental Variables.66 | Analytic Procedures.......67 | Descriptive Statistics..67 | Factor Analysis..67 | Multivariate Analysis of Variance (MANOVA)...69 | Regression Analyses..69 | Missing Data..71 | Limitations.72 | Chapter IV: FINDINGS.....75 | Research Question 1..75 | Research Question 2..83 | Research Question 3..85 | Research Question 4..98 | Summary..101 | Chapter V: SUMMARY AND DISCUSSION106 | Summary of the Study.....106 | Discussion and Implications for Practice.120 | Limitations...127 | Recommendations for Further Research..128 | Summary......129 | REFERENCES130 | APPENDIX A: Institutional Review Board Exemption Report..141 | APPENDIX B: Community Engagement Survey........143 | APPENDIX C: Request for Study Participation .........168 |
Keywords: Dissertations; Educational Leadership